2007
DOI: 10.1111/j.1651-2227.2007.00207.x
|View full text |Cite
|
Sign up to set email alerts
|

Vascular effects of sphingolipids

Abstract: We conclude that sphingomyelin metabolites are important endogenous modulators of vascular function, which may contribute to the pathophysiology of some diseases and be targets for therapeutic interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 64 publications
2
24
1
Order By: Relevance
“…25). Although signaling through S1P 2 and S1P 3 receptors has been shown to contribute to S1P-induced vasoconstriction (22,42,43), the present results obtained in S1P 2 and S1P 3 receptornull aortic VSMCs and in VSMCs in which S1P 1 was inhibited with VPC23019 demonstrate that S1P can signal either via other receptors or via intracellular mechanisms to induce SOCE.…”
Section: Discussioncontrasting
confidence: 46%
“…25). Although signaling through S1P 2 and S1P 3 receptors has been shown to contribute to S1P-induced vasoconstriction (22,42,43), the present results obtained in S1P 2 and S1P 3 receptornull aortic VSMCs and in VSMCs in which S1P 1 was inhibited with VPC23019 demonstrate that S1P can signal either via other receptors or via intracellular mechanisms to induce SOCE.…”
Section: Discussioncontrasting
confidence: 46%
“…Furthermore, dietary SM plays an important role in neonatal gut maturation during the suckling period of rats and contributes to the myelination of the developing rat central nervous system (CNS) (Oshida et al, 2003). Michel, Mulders, Jongsma, Alewijnse, and Peters (2007) also suggested that SM metabolites are important endogenous modulators of vascular function, which may contribute to the pathophysiology of some diseases.…”
Section: Polar Lipids Sphingolipids and Metabolitesmentioning
confidence: 99%
“…It already has been demonstrated that lysosphingolipids can affect cellular proliferation via interference in signal transduction. For example, sphingosine-1-phosphate is known to stimulate proliferation of smooth muscle cells by a variety of signal transduction pathways including ERK and MAPK (39,40).…”
Section: Discussionmentioning
confidence: 99%